Mirror Syndrome in Monochorionic Twin Pregnancy with Acardiac Fetus. (8th January 2018) - Ortiz, Luiz Felipe Lessa; Elito Júnior, Julio; Araujo Júnior, Edward; Peixoto, Alberto Borges; Sass, Nelson; Moron, Antonio Fernandes
Abstract : We report the case of a 20-year-old patient, primigravida, with twin monochorionic pregnancy, with a weight gain of 6 kg in one week and increased blood pressure. During the ultrasound diagnostic investigation, placental edema and hydrops were identified in both fetuses, which, in association with maternal anasarca and pressure control, constitute the triad for mirror syndrome, also known as triple edema. In addition to being hydropic, one of the twins was an acardiac fetus, which is a rare combination of events. Gestation was terminated at 22 weeks and five days because of high maternal risk. The patient progressed with clinical and laboratory improvement. Our study is relevant in that it documents an extremely rare case and discusses relevant aspects of the symptoms and diagnosis of mirror syndrome. It also systematically reviews the condition.